Chenopodium ambrosioides L. Improves Phagocytic Activity and Decreases Bacterial Growth and the Systemic Inflammatory Response in Sepsis Induced by Cecal Ligation and Puncture - Rios, Carlos E. P.; Abreu, Afonso G.; Braga Filho, Jose A. F.; Nascimento, Johnny R.; Guerra, Rosane N. M.; Amaral, Flávia M. M.; Maciel, Márcia C. G.; Nascimento, Flávia R. F. (Frontiers in Microbiology, 2017)
Chenopodium ambrosioides L. (Amaranthaceae) is often used in different kinds of vegetal preparations for medicinal purposes in many clinical situations. Some studies have demonstrated its anti-inflammatory and immunomodulatory properties. The aim of this work was to investigate the effect of prophylactic treatment with the hydroalcoholic extract of C. ambrosioides (HCE) and its hexanic fraction (HEX) on the control of bacterial growth, the activation of phagocytes and the control of the systemic inflammatory response in a sepsis experimental model. Animals were divided into three groups (n = 5/group): Control, which received only NaCl 0.9% solution; HCE, which received the crude extract; and HEX, which received the hexane fraction of the extract. The animals received saline, HCE or HEX (5 mg/kg), subcutaneously (SC), 6 h before cecal ligation and puncture (CLP). Twelve hours after the CLP, the blood was collected to measure the serum cytokines, and the animals were killed for the evaluation of colony-forming units (CFUs), cellular influx and activation of phagocytes in the peritoneal cavity, measured by the secretion of hydrogen peroxide and nitric oxide production. The results showed that only HEX treatment inhibited bacterial growth in the peritoneum and inflammatory cellular influx, especially influx of macrophages and neutrophils. However, HCE and HEX treatments increased ex vivo hydrogen peroxide secretion and nitric oxide production by phagocytes and decreased the pro-inflammatory cytokines in the serum, indicating a systemic anti-inflammatory effect of both. In conclusion, C. ambrosioides treatment decreases bacterial growth likely by activation of phagocytes and, in parallel, ameliorates the general state of mice by reducing the systemic inflammatory response usually observed in sepsis.